Design concept of a lightweight electric motor casing with support from thermomechanical simulations. (2016) - Müller, Timo; Blazek, Gustavo; Henning, Frank
Electric and hybrid electric vehicles and lightweight components are important issues for the automotive industry in the pursuit for the reduction of carbon emissions. In this study, a fibre-reinforced polymer (FRP) casing for a high-power electric motor was designed, with focus on the cooling system effectiveness. Heat transfer simulations were performed to prove the effectiveness of different proposed cooling systems. A design concept using the selected cooling system and 30 wt% glass fibre-reinforced polyamide-6 as the material for the casing was submitted to a thermomechanical analysis. Results show a maximum temperature of 105°C in the casing and stresses well within the limits of the material. For this material, the design concept shows a potential for 65% weight reduction. The possibility of using other FRPs is also briefly discussed.